Effects of inoculating with lignocellulose-degrading consortium on cellulose-degrading genes and fungal community during co-composting of spent mushroom substrate with swine manure. (November 2019) - Hu, Ting; Wang, Xiaojuan; Zhen, Lisha; Gu, Jie; Zhang, Kaiyu; Wang, Qianzhi; Ma, Jiyue; Peng, Huiling; Lei, Liusheng; Zhao, Wenya
Graphical abstract: Highlights: Microbial inoculation enhanced the diversity and richness of the fungal community. Inoculation changed the co-occurrence patterns of the fungal community. Inoculation led to higher abundances of the 18S rRNA and cellulose-degrading genes. Variations in cellulose-degrading genes were driven by fungal community succession. Abstract: Composting is used widely for recycling spent mushroom substrate (SMS). This study investigated the effects of inoculating a lignocellulose-degrading consortium at two levels comprising 0% (control: CK) and 10% (T) on the fungal community and cellulose-degrading genes during SMS co-composting with swine manure. Lignocellulose degradation rate in T was 8.77–34.45% higher compared with CK. Inoculation affected the distribution of the fungal community, increased the community diversity, and inhibited pathogens. Network analysis showed that inoculation changed the co-occurrence patterns of the fungal communities and made the co-composting system more stable. The relative abundances of glycoside hydrolase genes GH3E (fungal GH3), GH6, and GH7 were 0.45, 0.09, and 0.39 logs higher in T, respectively, than CK. Partial least-squares path modeling suggested that the variations in cellulose-degrading genes were driven mainly by changes in the fungal community during co-composting. Therefore, the lignocellulose-degrading consortium accelerated the transformation of lignocellulose to facilitate safer composting.